Morphology and Phylogeny of a New Species of Anaerobic Ciliate, Trimyema finlayi n. sp., with Endosymbiotic Methanogens - Lewis, William H.; Sendra, Kacper M.; Embley, T. Martin; Esteban, Genoveva F. (Frontiers in Microbiology, 2018)
Many anaerobic ciliated protozoa contain organelles of mitochondrial ancestry called hydrogenosomes. These organelles generate molecular hydrogen that is consumed by methanogenic Archaea, living in endosymbiosis within many of these ciliates. Here we describe a new species of anaerobic ciliate, Trimyema finlayi n. sp., by using silver impregnation and microscopy to conduct a detailed morphometric analysis. Comparisons with previously published morphological data for this species, as well as the closely related species, Trimyema compressum, demonstrated that despite them being similar, both the mean cell size and the mean number of somatic kineties are lower for T. finlayi than for T. compressum, which suggests that they are distinct species. This was also supported by analysis of the 18S rRNA genes from these ciliates, the sequences of which are 97.5% identical (6 substitutions, 1479 compared bases), and in phylogenetic analyses these sequences grouped with other 18S rRNA genes sequenced from previous isolates of the same respective species. Together these data provide strong evidence that T. finlayi is a novel species of Trimyema, within the class Plagiopylea. Various microscopic techniques demonstrated that T. finlayi n. sp. contains polymorphic endosymbiotic methanogens, and analysis of the endosymbionts’ 16S rRNA gene showed that they belong to the genus Methanocorpusculum, which was confirmed using fluorescence in situ hybridization with specific probes. Despite the degree of similarity and close relationship between these ciliates, T. compressum contains endosymbiotic methanogens from a different genus, Methanobrevibacter. In phylogenetic analyses of 16S rRNA genes, the Methanocorpusculum endosymbiont of T. finlayi n. sp. grouped with sequences from Methanomicrobia, including the endosymbiont of an earlier isolate of the same species, ‘Trimyema sp.,’ which was sampled approximately 22 years earlier, at a distant (∼400 km) geographical location. Identification of the same endosymbiont species in the two separate isolates of T. finlayi n. sp. provides evidence for spatial and temporal stability of the Methanocorpusculum–T. finlayi n. sp. endosymbiosis. T. finlayi n. sp. and T. compressum provide an example of two closely related anaerobic ciliates that have endosymbionts from different methanogen genera, suggesting that the endosymbionts have not co-speciated with their hosts.